PENINGKATAN KANDUNGAN SENYAWA FENOLIK DAN FLAVONOID PADA TEPUNG LENGKUAS MERAH (Alpinia officinarum) MELALUI OPTIMASI DURASI FERMENTASI DENGAN Lactobacillus plantarum - Mesa, Yanuarius; Fitasari, Eka; Rinanti, Rosyida Fajri; Setiawan, Ahmad Iskandar (BUANA SAINS, 2025)
Red galangal (Alpinia officinarum) is a medicinal herb rich in phenolic and flavonoid compounds, which offer significant health benefits. This study aimed to optimize the fermentation duration using Lactobacillus plantarum FNCC 0026 to maximize the bioactive content in red galangal flour. The research method involved fermenting red galangal flour for periods ranging from 1 to 7 days, followed by drying and a staged maceration extraction using 70% ethanol. The analyzed parameters included the final pH of the fermentation medium, total phenolic content (TPC), and total flavonoid content (TFC). The results indicated that a longer fermentation period decreased the pH, although no significant differences were observed among the 1- to 7-day treatments. Otherwise, the fermentation duration had a highly significant effect on TPC (p0.01) and TFC (p0.05). The highest accumulation of both TPC and TFC was achieved after 5 days of fermentation, with values of 1468.78 mg GAE/100 g and 41.49 mg QE/100 g, respectively. It is concluded that a 5-day fermentation period is the optimal duration for enhancing the bioactive compounds in red galangal, offering an effective biotechnological approach for developing functional food ingredients.